Current treatment patterns within 1 year after prostate cancer diagnosis in Korean patients over 75 years old: a retrospective multicenter study - Dong Jin Park; Ho Won Kang; Se Yun Kwon; Young Jin Seo; Kyung Seop Lee; Byung Hoon Kim; Teak Jun Shin; Won Tae Kim; Yong-June Kim; Seok Joong Yun; Sang-Cheol Lee; Jae-Wook Chung; et al. (Prostate International, 2023)
Background: We aimed to evaluate the current status of first-line treatment options for prostate cancer in patients aged ≥75 years in Korea. Materials and methods: The study included 873 patients diagnosed with biopsy-proven prostate cancer at 5 institutions in Korea from January 2009 to December 2018. Inclusion criteria were aged ≥75 years at diagnosis, prostate biopsy with ≥12 cores, and follow-up period ≥1 year. Clinical data were retrospectively collected from electronic medical records. Results: Primary treatment for prostate cancer in patients aged ≥75 years included androgen deprivation therapy (ADT) (n = 614), radical prostatectomy (RP) (n = 114), and radiation therapy (n = 62). Among patients with RP, nine patients received ADT before RP. The RP group was younger with better Eastern Cooperative Oncology Group Performance Status (ECOG PS), lower initial prostate-specific antigen (PSA), Gleason score (GS), max percent positive cores, less positive cores, and less advanced clinical Tumor Node Metastasis (TNM) stage compared with the ADT group. Multivariate analysis showed that age, ECOG PS, and PSA were independent prognostic factors for RP. When the ADT group was classified by therapeutic regimens, the most common therapeutic regimen was maximal androgen blockade (MAB) (n = 571), and leuprolide + bicalutamide (n = 330) was the most common MAB regimen. Multivariate analysis for secondary treatment showed that age, ECOG PS, GS, and clinical N1 or M1 stage were independent predictive factors. Enzalutamide was the most preferred treatment for tertiary treatment. Conclusion: In patients with prostate cancer aged ≥75 years, the most common treatment option was MAB, and the leuprolide + bicalutamide was the most common MAB regimen. Age, ECOG PS, and PSA are the useful indicators of surgical treatment, which increased during the study period. Younger patients with high GS and advanced clinical stage were more likely to undergo secondary treatment.